Signal analysis of vibration measurements for condition monitoring of bearings - Chebil, Jalel; Hrairi, Meftah; Abushikhah, Nazih (INSInet Publications, 2011)
Rotating machinery is a common class of machinery in industry. The root cause of faults in rotating machinery is often faulty rolling element bearings. These rolling element bearings wear out easily due to the metal-metal contacts and create faults in the outer race, inner race, or balls. This study compares several techniques used for monitoring bearing condition. These techniques are based on the processing of vibrational data in the time-domain, frequency-domain, or time-frequency-domain. It was found that the discrete wavelet transform which is based on time-frequency analysis produces the best results.